The discourse of lack and the representation of the writer’s conflicts in times of political turbulence in «El lamento del sargento de Aguas Verdes» («The lament of the sergeant of Aguas Verdes») and 2046 - Herrera Castro, Maryori Alma (2024)
This article will explore how the discourse of deprivation runs through the configuration of the writer character in the poem «El lamento del sargento de Aguas Verdes» («The lament of the sergeant of Aguas Verdes» (1974), by Jorge Pimentel, and in the film 2046 (2004), directed by Wong Kar-wai. The selected texts comprise the representation of writing characters whose life experiences related to deprivation differ from one another, affected by gender, race, social class, culture and socio-political context. The aim of this paper is to find points of comparison, in that it identifies constancies in the types of conflicts faced by the writers and understands the impact that the aforementioned points of divergence may have on how deprivation and its consequences are dealt with. It is proposed that there is a constancy of economic deprivation that underpins the repetition of the act of writing, and also the total dependence of the writer, who suffers from deprivation, on the means of publication and dissemination of his work. This dependence makes him vulnerable to a demand that can lead to the mechanisation of his work and, therefore, to the dehumanisation of the writing subject. For this purpose, the Semiotics of discourse (2001) by Jacques Fontanille and the Semiotics of the filmic text (2003), proposed by Desiderio Blanco, will be used in such a way that, on the basis of the tensions, it will be possible to establish a semi-symbolic relationship that shows the intention of a particular treatment of the conflicts of each writer character and, in the same way, a series of similarities despite the differences of expression in their respective media.